The Influence of Technology Orientation, Human Resources Readiness, and Management Support on Digital Competence and its Implications for Mining Operational Team Performance (Case Study at PT Petrosea TBK) - Praeditia, Yoppi Adhi; Sutjipto, Mohammad Riza (International Journal Labs, 2025)
This study examines the impact of technology orientation, human resource readiness, and management support on digital competency and its implications for operational team performance at PT Petrosea Tbk, a mining services company undergoing digital transformation via the Minerva platform since 2018. Despite ongoing efforts, team performance in productivity, efficiency, and quality remains inconsistent. Using a quantitative approach, data were collected from 72 operational team leaders through proportionate stratified random sampling and analyzed using PLS-SEM via SmartPLS 4. The results show that management support (? = 0.406; p < 0.01), technology orientation (? = 0.319; p = 0.02), and HR readiness (? = 0.235; p = 0.017) significantly influence digital competency. In turn, digital competence (? = 0.374; p = 0.01) significantly enhances operational team performance and mediates the relationship between all independent variables and performance outcomes. The R² values of 0.551 for digital competency and 0.715 for team performance indicate a moderately strong model. This study contributes to the digital transformation literature in the mining sector by empirically validating how internal organizational resources and capabilities drive performance through digital competence. Practical recommendations include enhancing training for data analysis and platform usage, strengthening management’s digital support role, and improving technological accessibility and innovation.